(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Nefopam hydrochloride (Acupan) is commonly used to relieve moderate to severe postoperative pain. This drug is generally well tolerated; however, it has been associated with cardiac conduction problems, cerebral edema, fever, and renal failure when taken in excess. The aim is to investigate the effect of toxic doses of nefopam on the liver, heart, and brain of rats after exposure (acute toxicity of nefopam and concentration in these organs. Demonstrate whether TNF-α and NF-κB, and some selected interleukins (IL1β and IL-10) have a role in the mechanism of organ injury induced by nefopam Methods: Fourteen(14) adult rats, Group I controls n = 7: Rats were administered a single intraperitoneal injection (IP) with normal saline Group II Nefopam-treated animals: each rat injected with a one toxic dose IDP (40 mg/kg) Nefopam and then sacrificed 24 hours after drug administration, and whole blood and organs were collected. Results: After injection of a toxic dose of nefopam showing a decrease in serum level of TNF-α (17.96 Pg per ml to 14.53 Pg per ml) and a decrease in IL 10 (from 36.26 to 23.22) and IL from (6.0 to 5.3 pg/ml) and an increase in NF-κB (396.314 TO 416.266 Pg/ml), the cardiac marker also changed CK-MB. Conclusion: Nefopam(acute toxic model) produced various effects on serum levels of cytokines (whether inflammatory or anti-inflammatory markers), in addition, it did not have significant effects on CK-MB, ALT, AST, and ALP; this may indicate that this acute toxic dose of Nefopam did not have significant effects on heart and liver tissues.